THE ANALYSIS OF ROLLS ROYCE IN THE PERSPECTIVE OF INTERNATIONAL HUMAN RESOURCE MANAGEMENT AND CROSS-CULTURAL DIFFERENCES - Ahmad Jawid Jamali (Journals Park Publishing, 2022)
Culture is such a significant factor in the expansion of business beyond borders in a global scale which can influence organizations and businesses in all walks of the activities. In the context of cross-cultural differences, dissimilarities in culture and language create communication and other related issues that leads to inter- organizational obstacles that can affect the business overseas.This paper hypothetically examines the main activities of the human resource department of the British Multinational company Rolls Royce in a simulated scenario of expansion in Uzbekistan within the framework of cross-cultural issues. All significant rituals done by HR departments such as Recruitment and selection, Reward and Retention as well as Training and Development have been critically discussed in details. Furthermore, at the end of the paper recommendations have been given by the writer.Expansion of Business in a country with different beliefs, culture and values requires higher consciousness and precision. It should move on paralleled with research, planning, smart execution, analyzing weak points and developing strategies to fill the gaps and improve the work. Experimented management practices along with best of human resources are the other significant elements. Culture is such a phenomenon which tends to be changing from time to time that we can notice it when we tap into our societies looking at it based on periodical perspectives. An accepted manner in a culture may turn to change its color and become unaccepted in the society. Finding a ready-made remedy to cope with cultural difference is not the perfect right choice.
Keywords: Cross-Cultural differences, International human resource management, Organizational culture